Short-term association of in-vehicle ultrafine particles and black carbon concentrations with respiratory health in Parisian taxi drivers. (February 2021) - Hachem, Melissa; Loizeau, Maxime; Saleh, Nadine; Momas, Isabelle; Bensefa-Colas, Lynda
Graphical abstract: Abstract: Introduction: Professional drivers are exposed inside their vehicles to high levels of air pollutants due to the considerable time they spend close to motor vehicle emissions. Little is known about ultrafine particles (UFP) or black carbon (BC) adverse respiratory health effects compared to the regulated pollutants. Objectives: We aimed to study the short-term associations between UFP and BC concentrations inside vehicles and (1) the onset of mucosal irritation and (2) the acute changes in lung function of Parisian taxi drivers during a working day. Methods: An epidemiological study was carried out on 50 taxi drivers in Paris. UFP and BC were measured inside their vehicles with DiSCmini® and microAeth®, respectively. On the same day, the frequency and the severity of nose, eye, and throat irritations were self-reported by each participant and a spirometry test was performed before and after the work shift. Multivariate analysis was used to evaluate the associations between in-taxis UFP and BC concentrations and mucosal irritation and lung function, after adjustment for potential confounders. Results: In-taxis UFP concentrations ranged from 17.9 to 37.9 × 10 3 particles/cm 3 and BC concentrations from 2.2 to 3.9 μg/m3, during a mean of 9 ± 2 working hours. Significant dose-response relationships were observed between in-taxis UFP concentrations and both nasal irritation and lung function. The increase of in-taxis UFP (for an interquartile range of 20 × 10 3 particles/cm 3 ) was associated to an increase in nasal irritation (adjusted OR = 6.27 [95% CI: 1.02 to 38.62]) and to a reduction in forced expiratory flow at 25–75% by −7.44% [95% CI: −12.63 to −2.24], forced expiratory volume in one second by −4.46% [95% CI: −6.99 to −1.93] and forced vital capacity by −3.31% [95% CI: −5.82 to −0.80]. Such associations were not found with BC. Incident throat and eye irritations were not related to in-vehicle particles exposure; however, they were associated with outdoor air quality (estimated by the Atmo index) and in-vehicle humidity, respectively. Conclusion: To our knowledge, our study is the first to show a significant association, within a short-period of time, between in and vehicle UFP exposure and acute respiratory effects in professional drivers.